ANALISIS LINGKUNGAN PERAIRAN UNTUK ZONA PENGEMBANGAN BUDIDAYA LAUT DI TELUK GERUPUK KABUPATEN LOMBOK TENGAH - PUTRA, AGUS MULIADI; Budiarsa Suyasa, I.W.; Mahendra, M.S. (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science); Vol 7 No 1 (2012), 2012)
This research aims to identify the water suitability and carrying capacity level based on marine culture activity used. The research treated on May to July 2011 at Gerupuk Bay, Subdistrict of Pujut, Central Lombok Regency. The methods used in this research are analyzing the parameter, processing the data, and analyzing the data based spatial named Geographic Information System (GIS). This analysis proves that Gerupuk Bay might be used as marine culture development area with total area 339,768 Ha. Highly suitable area with 60,343 Ha, is for seaweeds area. For grouper fish most of the area is marginally suitable area with 99,198 Ha, for moderately suitable is 68,105 Ha and for unsuitable area found is 112,122 Ha. After identifying the data, the total maximum carrying capacity area for seaweeds activity is 8 units for long line which 7 units (87,5%) have been used, and 18 units for floating raft method which 10 units (55,5%) have been used. The maximum total unit for the grouper fish is 26 units for net floating cages method whlch only 1 unit (4%) has been used. Finally, the conclusion of U1is research is that the water environmental for each marine culture activity is less then 50% of all area. For lhe estimation of the maximum carrying capacity of grouper fish is less then 50%, in other hand the maximum carrying capacity of seaweeds is up to 50%.
Keywords: Environmental parameter, Zoning, Marine culture, Gerupuk Bay